Assessment of municipal solid waste management system in a developing country - Ahsan, Amimul; Alamgir, M.; El-Sergany, Moetaz M.; Shams, S.; Kamal, Md. Rowshon; Nik Daud, Nik Norsyahariati (Hindawi Publishing Corporation, 2014)
This study represents a few basic steps of municipal solid waste management practiced in the six major cities of Bangladesh, namely, Dhaka, Chittagong, Khulna, Rajshahi, Barisal, and Sylhet. A six-month field study was conducted to identify the solid wastes management steps such as storage at source, separation, on-site storage, collection, transportation, treatment, reuse, recycling, and ultimate disposal. This study addresses the role of the city authority to meet the demand of the city dwellers in solving this emerging socioenvironmental issue and the initiatives taken by some nongovernmental organizations and community based organizations. The problems and constraints of the solid wastes management system are also identified to find a sustainable management concept for the urban areas of Bangladesh.